The Prevalence of Antiretroviral-Therapy-related Adverse Reactions, Hospitalisation, and Mortality among People Living with HIV in Africa-A systematic review and Meta-Analysis - Moirana, Elizabeth Lorivi (Department of Public Health and Family Medicine, 2023)
Introduction: Medicines are an important component of any health system. Even though the importance of medicines in the health system is indisputable, one of the major concerns remains the risk of adverse drug reactions when used by consumers. Adverse drug reactions place a burden on the healthcare system, usually as a result of complications requiring hospital admission or extended hospital admissions. In Africa, about 28.6% of adverse drug reactions reported in Africa were due to antiretroviral therapy. Recently, the adoption of the “test and treat” policy by the World Health Organisation increased the number of people receiving antiretroviral therapy. Therefore, this systematic review was conducted to explore the magnitude of antiretroviral therapy-related adverse drug reactions hospitalisations, and mortalities in the region, following the increase in people initiating therapy, and the implications to the service delivery component of the healthcare system. Methods: In March 2021, PubMed, EBSCOHost, and SCOPUS, databases were systematically searched for appropriate articles. The selection of articles was based on predefined inclusion and exclusion criteria. Data from included articles were extracted as per a set of defined criteria into a data extraction form. A meta-analysis was done using Stata package software 15.0 using Stata “metaprop” command. Results: The pooled prevalence of adverse drug reactions hospitalisations in all studies was 26.5% (95% confidence interval:18.4,35.4) and that of mortality was 6.1% (95% confidence interval:2.1,11.7). The most prevalent adverse reactions reported include hepatotoxicity, kidney injury, lactic acidosis, skin, neurologic, and hematologic reactions. The antiviral implicated, are non-nucleoside reverse transcriptase inhibitors, nucleoside/tide reverse transcriptase inhibitors, and protease inhibitors. The pediatric population was underrepresented as only two studies included pediatric patients. The economic impact of adverse reactions was impossible to estimate, as only one study reported on financial implications. Conclusion: Antiretroviral therapy-related adverse reactions hospitalisations and mortalities have a high prevalence in Africa. There are concerns about age-related morbidities and lifestyle diseases as risk factors related to adverse reactions. To adequately combat adverse reactions associated with antiretrovirals, African country health systems need multidisciplinary actions to strengthen strategies for prediction, identification, reporting, and prevention of adverse reaction occurrence.